Essentials of Risk Theory
XI, 148 p.
Keywords: Risk has become one of the main topics in fields as diverse as engineering, medicine and economics, and it is also studied by social scientists, psychologists and legal scholars. This Springer Essentials version offers an overview of the in-depth handbook and highlights some of the main points covered in the Handbook of Risk Theory. The topic of risk also leads to more fundamental questions such as: What is risk? What can decision theory contribute to the analysis of risk? What does the human perception of risk mean for society? How should we judge whether a risk is morally acceptable or not? Over the last couple of decades questions like these have attracted interest from philosophers and other scholars into risk theory. This brief offers the essentials of the handbook provides for an overview into key topics in a major new field of research and addresses a wide range of topics, ranging from decision theory, risk perception to ethics and social implications of risk. It aims to promote communication and information among all those who are interested in theoretical issues concerning risk and uncertainty. The Essentials of Risk Theory brings together internationally leading philosophers and scholars from other disciplines who work on risk theory. The contributions are accessibly written and highly relevant to issues that are studied by risk scholars. The Essentials of Risk Theory will be a helpful starting point for all risk scholars who are interested in broadening and deepening their current perspectives. .